Impact of digital transformation on the development of new business models and consumer experience - Rodrigues, Maria Antonia, 1977-; Proença, João F. (Advances in business strategy and competitive advantage., 2022)
"This book presents research findings and an innovative and multifaceted perspective of how digital transformation and other innovative technologies can drive new business models and create value experiences for consumers and/or firms"--